SERUM IRON, ZINC AND COPPER STATUS OF SEVERELY MALNOURISHED CHILDREN IN WAD MEDANI, SUDAN - Abdalla, Areeg saad; Babikir, Hayder Elhadi; Ali, Khalid Eltom (Gezira Journal of Health Sciences, 2005)
Objective: To determine status of iron (Fe), zinc (Zn) and copper (Cu) in severely malnourished children in Wad Medani, Central Sudan. Methods: Atomic absorption spectrophotometry was used to assess the serum concentrations of iron, zinc and copper in ninety children- sixty severely malnourished children and thirty control. The children were selected randomly from patients admitted to the nutritional section at Wad Medani Children Teaching Hospital in Gezira State, Central Sudan. The age range of the studied children was 3-37 months. The malnourished children were diagnosed and classified into two groups: marasmus and kwashiorkor with 30 patients in each group. Their anthropometric measurements including weight and height were measured. Total serum  protein, serum albumin, haemoglobin concentrations and haematocrit were determined using standard methods. Results: Analysis of variance between the three groups showed highly significant differences in all measured biochemical parameters (p<0.001). Positive and significant correlations were observed between serum albumin and zinc levels (r = 0.4, p=0.01), and between serum copper and haemoglobin levels (r = 0.3, p=0.01). The nature of the association between these trace elements status and their implications for malnutrition pathophysiology are discussed.